Single incision laparoscopic surgery - incisional hernia repair - Kirac, Iva (Endoskopska revija, 2009)
Advancement in technology enabled a surge of single incision laparoscopic surgery (SILS). We introduce incisional hernia repair into the scope of SILS operations. Main argument in favour of this idea is that every incision and trocar placement presents a risk for bleeding, organ damage, decreases cosmesis and is another potential site of incisional hernia. We operated on a 57 year old female patient who presented with right periumbilical incisional hernia. Single incision laparoscopic dual mesh repair was performed: a single 2,5 cm incision was made, at the level 2 cm above umbilicus in left anterior axillary line. We used 10 mm optical trocar (angled camera with a working port) and one 5 mm trocar placed 1 cm cranially from the optical port. Operation was without complications, operating time being 65 minutes. Postoperative recovery was uneventful. We report, what is to our knowledge, the first experience with single incision laparoscopic incisional hernia repair. Based on this and our previous experiences with SILS we believe that SILS incisional hernia repair is feasible in selected patients and that this approach should have less morbidity compared to other approaches. It remains to be compared with standard laparoscopic incisional hernia repair in terms ofpatient recovery, reduction of postoperative pain, complication rate, recurrence rate and port site hernia.
Keywords: Hernija umbilikalna; Surgery, Laparoscopic; Kirurška mrežica; Methods; Srednja leta; Hernia, Umbilical; Surgery; laparoskopska kirurgija; Surgical Mesh; hernija; kirurško zdravljenje; Middle Age